Optimization Of Microwave-Assisted Extraction Of Flavonoids From Binahong (Anredera cordifolia) Leaves Using Respon Surface Methodology - Zaldy Rusli; Bina Lohita Sari; Novi Fajar Utami; S Sabila (Jurnal Fitofarmaka Indonesia, 2020)
Binahong (Anredera scandens (L.) Moq.) leaves are one of the plants that empirically can be used for wound healing and contain flavonoids which have antibacterial and antioxidant activities. Determination of the optimum conditions of the Binahong leaf extraction process needs to be done to ensure the extraction quality of the Binahong leaves associated with the given activity. Microwave Assisted Extraction (MAE) is an extraction that utilizes microwave radiation to heat the solvent quickly and efficiently. This study aims to determine the most effective binahong leaf extraction conditions that produce optimal levels of flavonoids and antioxidant activity. The extraction process was carried out using the Microwave assisted extraction (MAE) method. Determination of optimum conditions is done based on Response Surface Method (RSM) with variable ethanol concentration (70%, 80% and 90%), extraction time (4, 12 and 20 minutes) and power (450, 600, and 800 watts) using Box- Behnken Design (BBD) with Design Expert 7.0 software. The extract quality parameters measured were total flavonoid levels and antioxidant activity. The results showed the optimum conditions with the BBD method were obtained at an ethanol concentration of 81.49%, extraction time of 13.84 minutes, and power of 626.19 watts with flavonoid levels of 3.8561% and antioxidant activity (IC50) of 95.51834 ppm with active categories.